Intercultural communication and adolescent learners: a corpus-based approach to online and face-to-face interaction - Lin, Yen-Liang (2013)
This study reports on a corpus analysis of samples of online and face-to-face intercultural communication among a group of British and Taiwanese adolescents, with the aim of exploring the particular lexical, grammatical and discourse features of the online and spoken discourse from three perspectives: a keyness approach, a discourse analytical perspective and a multi-word sequence perspective. Keyness approach brings together three levels of keyness analysis: keywords, semantic domains and parts-of-speech, and further highlights those linguistic features that deserve particular attention. Furthermore, a discourse analytical approach adds greater detail and depth of description of language patterning by examining the particular linguistic features in context. Such findings that pertain to discourse and pragmatic functions in context are not likely to be made when only keyness is examined. The third approach of this thesis focuses on recurrent multi-word sequences, paying particular attention to their discourse functions in online and spoken settings. It is evident that multi-word sequences often perform systematic discourse functions, even though they do not usually constitute complete grammatical or idiomatic structures. The approach also examines the developmental perspectives of multi-word sequences, showing that intercultural contact with native speakers of English fosters the longitudinal development of the use of sequences by the Taiwanese learners. The method here, which focuses on naturally occurring language output, diminishes the effects of the artificial contexts often created in language testing settings. In light of the potential significance of the research to EFL pedagogy, the thesis further reports on the extent to which EFL textbooks used in Taiwan represent the particular linguistic features identified in authentic intercultural communication. The research findings demonstrate the pedagogical merit of the analyses of the three perspectives and thus help in the design of courses for adolescent intercultural interaction in both online and face-to-face settings.